Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2012
DOI: 10.1111/j.1600-0609.2012.01783.x
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for tissue iron overload in long‐term hemodialysis patients and the impact of withdrawing parenteral iron

Abstract: Background/aims Erythropoiesis in long‐term hemodialyzed (LTH) patients is supported by erythropoietin (rHuEpo) and intravenous (IV) iron. This treatment may end up in iron overload (IO) in major organs. We studied such patients for the parameters of IO in the serum and in major organs. Methods Patients were treated with rHuEpo (6–8 x 103 units × 1–3/wk) and IV 100 mg ferric saccharate. Results Of 115 patients, 21 had serum ferritin (SF) > 1000 ng/mL. This group was further analyzed. Their SF and transferrin s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
128
0
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 97 publications
(140 citation statements)
references
References 38 publications
(41 reference statements)
8
128
0
4
Order By: Relevance
“…Most hemodialysis patients receiving ESA and IVI supplementation have excessive hepatic iron on magnetic resonance imaging. 44,45 In a study that closely followed guidelines for ESA administration and iron supplementation, 80% of the patients had excessive iron in the liver on magnetic resonance imaging and 30% had severe liver iron overload. 45 A 2009 study including 96 hemodialysis patients using bone marrow biopsy showed that most patients with ferritin levels of .500 ng/ml had higher levels of C-reactive protein and an increased content of bone marrow iron.…”
Section: Assessment Of Iron Storesmentioning
confidence: 99%
See 1 more Smart Citation
“…Most hemodialysis patients receiving ESA and IVI supplementation have excessive hepatic iron on magnetic resonance imaging. 44,45 In a study that closely followed guidelines for ESA administration and iron supplementation, 80% of the patients had excessive iron in the liver on magnetic resonance imaging and 30% had severe liver iron overload. 45 A 2009 study including 96 hemodialysis patients using bone marrow biopsy showed that most patients with ferritin levels of .500 ng/ml had higher levels of C-reactive protein and an increased content of bone marrow iron.…”
Section: Assessment Of Iron Storesmentioning
confidence: 99%
“…80 To our knowledge, the long-term effect of IVI administration to patients with elevated baseline serum ferritin levels upon surrogate markers of atherosclerosis, immune function, inflammation, and vascular reactivity also remain unstudied. However, a recent study in which 19 of 21 (90.5%) long-term dialysis patients with serum ferritin .1000 ng/ml had evidence of increased oxidative stress as well as splenic and hepatic tissue iron overload 44 suggests caution.…”
Section: Safety Signals In Epidemiology Studiesmentioning
confidence: 99%
“…During the same period in which we performed the last large study on CHD [24], we also analyzed in our laboratory CHD samples from another dialysis center using a different policy as regards to intravenous iron supplementation. In this particular setting, including selected CHD patients with MR-ascertained iron overload and serum ferritin levels > 1000 μ g/L [18], we observed serum hepcidin levels substantially higher than controls even after careful matching using the same criteria outlined above for the patients enrolled in Milan [24]. In agreement with the view that iron status rather than uremia per se appears as the major determinant of hepcidin in CHD, serum ferritin was the major predictor of hormone level in nearly all the studies published so far, which also included CRP as covariate (Table 1).…”
Section: Hepcidin As a Player In The Anemia Of Chdmentioning
confidence: 99%
“…These studies also strongly suggest a link between the IV iron dose and the risk of iron overload in this setting, challenging current guidelines with respect to the influence on LIC of IV iron products at high repeated doses [4,8,17,18,59,60], as well as the reliability of iron biomarker cutoffs, and methods for monitoring iron stores in dialysis patients [8,9,15,16]. Two recent MRI studies have focused on iron overload in hemodialysis patients with serum ferritin levels far above 500 mg/L [60]. Pancreatic involvement was sought in only 8 most overloaded patients and was found in 3 cases (37%) [60].…”
Section: Noninvasive Imaging Of Liver Iron Stores By Mri: Specific Fementioning
confidence: 99%
“…Radiologists and nephrologists should realize that there are marked differences in the pharmacokinetics of IV iron products, and that these can interfere with MRI (tables II and III) [57]. The required time interval between the last IV iron infusion and MRI should range from one week (iron sucrose, iron gluconate, iron carboxymaltose) to one month (low-molecularweight iron dextran and iron isomaltoside), 3 months (highmolecular-weight iron dextran) or even 6 months (ferumoxytol) if spurious results due to magnetic interference are to be avoided ( Iron overload in dialysis patients in the ESA era Studies using superconducting quantum interference device (SQUID) thirteen years ago [11] and more recent studies employing quantitative MRI [8,59,60] to estimate LIC in hemodialysis patients, have provided new information on iron metabolism in ESRD and have underlined the risk of hemosiderosis. These studies also strongly suggest a link between the IV iron dose and the risk of iron overload in this setting, challenging current guidelines with respect to the influence on LIC of IV iron products at high repeated doses [4,8,17,18,59,60], as well as the reliability of iron biomarker cutoffs, and methods for monitoring iron stores in dialysis patients [8,9,15,16].…”
Section: Noninvasive Imaging Of Liver Iron Stores By Mri: Specific Fementioning
confidence: 99%